Perbedaan Qira’āt Menurut Sarjana Orientalis dan Muslim dan Implikasinya terhadap Penafsiran - Rohmansyah (Universitas Islam Negeri Madura, 2025)
One of problem discussed among scholars including orientalists is the difference in qira'at which has implications for interpretation in various aspects. This study aims to explain some opinions of orientalist scholars and Muslim scholars in response to the difference in qira'at. In addition, the study aims to see and analyze the implications of the difference in qira'at in several interpretations. The research method used is a qualitative method based on library research data with a descriptive-analytical approach. The findings of this study state that according to orientalists, the difference in qira'at will cause contradiction and chaos in determining the law. Meanwhile, according to Muslim scholars, differences in qira'at are a form of variation that will not alter the legal substance of the Quran. Besides that, there will be no conflict, change, or even chaos, because the Prophet conveyed qira'at according to the dialects of each tribe and nation. However, the difference in qira'at will have implications for four things, namely theological problems, fiqhiyah problems, gender equality problems, and miracle of the Qur’an itself.